Is muscle-strengthening exercise associated with better academic performance of Literacy, Mathematics and Language? Results from a cross-sectional study - Zhenyu Cen; Kai Zhang; José Francisco López-Gil; Xingyi Yang; Chunxiao Li; Sitong Chen (Journal of Exercise Science & Fitness)
Objectives: The aim of this study was to assess the associations of muscle-strengthening exercise (MSE) with academic performance (AP) of different subjects in Chinese school-aged children and adolescents. Methods: Cross-sectional data on 67,281 students were included. Engagement in MSE was assessed using a specific question, and AP was assessed through self-reported grade in Literacy (Chinese), Mathematics, and Language (English). The analysis explored the associations between days of engagement in MSE and AP in Chinese, Mathematics, and English, separately. Results were presented as odds ratios (ORs). Results: There was a generally progressive increase in the likelihood of better AP of Chinese, Mathematics and English with increase in days of MSE. Specifically, one day of MSE per week was associated with an 11 % increase of better AP in Chinese, with a gradual increase up to 4 days per week (OR = 1.42), peaking at 6 days. The odds of enhanced AP related to Mathematics increased with days of MSE, starting with a 9 % increase for 1 day per week (OR = 1.09), and reaching a 39 % increase at 4 days per week. The odds of improved AP in English were 9 % higher for 1 day per week of MSE and continued to a 31 % increase for 4 days per week. Conclusion: This study suggests the potential positive role of MSE in enhancing AP in children and adolescents. Future studies are needed to confirm our findings based on longitudinal or intervention studies.